Strategic behavior and ambidexterity: a study applied along the Brazilian wineries - Silveira-Martins, Elvis; Rosseto, Carlos Ricardo; Lima, Nilton Cesar; Penedo, Antonio Sergio Torres (Review of Business Management, 2014)
The aim of this paper was to correlate the strategic behavior of managers of national winery industries with the process of organizational ambidexterity. Therefore, the theory adopted was mainly based on the knowledge of Miles and Snow (1978) on types of behavior, and March (1991), with respect to ambidexterity. The methodology used was the quantitative research, using the survey method. The sample consisted of 150 industries Brazilian wineries. To process the data, we used multivariate techniques, particularly structural equation modeling. The results point to a positive relationship between the prospector, anlyzer and reactor behaviors toward ambidexterity. The defender behavior has a negative relationship with ambidexterity. While this type is not theoretically related to the ambidextrous processes, the national wine industry scenario is empirically permeated by the need for reorganization, given the environmental situation experienced by the companies. The behavior of managers is influenced by reactive practices; for instance, we observe research on the need for measures to safeguard the market, which is conducted by the Ministry of Development, Industry and Foreign Trade (MDIC). Finally, the research stands out for addressing a specific theme and exploring its features, contributing to the literature, generating support for management decisions and expanding horizons for further research.